La comunicación política en la red social Instagram del candidato presidencial Guillermo Lasso y su impacto en los comicios en la segunda vuelta electoral del año 2021 - Vinueza León, Brigith Samantha (2022)
Political communication over the years has been adapting to different media, among which are the social networks that belong to the web 2.0, therefore, Instagram, is no exception as it is one of the fastest growing networks in the world and in Ecuador is no exception. In this sense, the present degree work, aims to investigate the political communication in the social network Instagram of the presidential candidate Guillermo Lasso and its impact on the elections in the second round of elections in the year 2021, one of the most voted candidates in the past electoral contests that the country lived. During the campaign period of the second electoral round that began on March 16 until April 11, 198 publications were collected in the Instagram profile of Guillermo Lasso, which based on a literature review were chosen study models and from this, I raised variables under a qualitative approach, and by virtue of this to know the type of content, publications, frequency of publications, hashtags, words, types of content and level of engagement and post generated, through a descriptive analysis.